2015
DOI: 10.1177/2058460115603420
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of ultrasound elastography for the quantification of transversus abdominis elasticity

Abstract: BackgroundThe transversus abdominis (TrA), which is considered to be involved in controlling spinal stability, is covered by two muscles (i.e. the external and internal oblique muscles) as well as subcutaneous fat. Therefore, there were doubts about whether it was possible to perform highly reliable measurements of muscle elasticity.PurposeTo investigate the reliability of ultrasound elastography for the quantification of elasticity of the TrA.Material and MethodsA skilled and an unskilled operator of ultrasou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 12 publications
2
17
0
1
Order By: Relevance
“…Lacourpaille et al have that reliability levels for SWE ranged from fair to excellent (ICC, 0.421–0.950) in a study including 9 different muscles (gastrocnemius medialis, tibialis anterior, vastus lateralis, rectus femoris, triceps brachii, biceps brachii, brachioradialis, adductor pollicis obliquus and abductor digiti minimi). Hirayama et al reported that the intraobserver reliability of SWE in the transversus abdominis muscle ranged from fair to excellent (ICC, 0.59–0.86); however, the interobserver reliability ranged from fair to good (ICC, 0.56–0.57). Cortez et al reported that the medial gastrosoleus and tibialis muscles had fair to good levels of intraobserver (ICC, 0.42–0.70) and interobserver (ICC, 0.69–0.73) reliability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lacourpaille et al have that reliability levels for SWE ranged from fair to excellent (ICC, 0.421–0.950) in a study including 9 different muscles (gastrocnemius medialis, tibialis anterior, vastus lateralis, rectus femoris, triceps brachii, biceps brachii, brachioradialis, adductor pollicis obliquus and abductor digiti minimi). Hirayama et al reported that the intraobserver reliability of SWE in the transversus abdominis muscle ranged from fair to excellent (ICC, 0.59–0.86); however, the interobserver reliability ranged from fair to good (ICC, 0.56–0.57). Cortez et al reported that the medial gastrosoleus and tibialis muscles had fair to good levels of intraobserver (ICC, 0.42–0.70) and interobserver (ICC, 0.69–0.73) reliability.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Although SWE has been used in studies conducted on individuals with muscle and tendon injuries and healthy individuals, contradicting results have been reported about the reliability of SWE. [13][14][15][16][17] The aim of this study was to determine intraobserver, interobserver, and interday reliability levels for measurements by SWE in the patellar tendon and rectus femoris muscle in healthy sedentary male individuals.…”
mentioning
confidence: 99%
“…Moreau et al () found a SM of 8.6 kPa (shear modulus) at level L2–L3 and 6.9 kPa at level L4–L5 in the multifidus at rest in prone position using SWE, and Chan et al () found a YM of 36 kPa, which corresponds to SM = 12 kPa, using strain elastography. By extension to other trunk muscles, mean stiffness using SWE ranged from 3.5 kPa for the internal oblique to 22 kPa for the external oblique (Hirayama et al, ; Tran et al, ). Such variability could result from significant interindividual and intermuscular stiffness differences.…”
Section: Discussionmentioning
confidence: 99%
“…force) and strain (deformation). A growing body of literature demonstrates the utility of SWE method for assessing muscle stiffness [3][4][5][6][7][8][9][10][11][12]. The shear modulus obtained with SWE has been validated for assessing muscle stiffnes, by using isolated meat speciments and comparing it to direct mechanical stiffness measures.…”
Section: Introductionmentioning
confidence: 99%